Sharia bank policy strategy in improving public interest in becoming customers at PT. Bank Muamalat Binjai branch - Aswin Fahmi D; M. Radiansyah; Aminullah Marlis Tanjung; M. Guffar Harahap (Institute of Computer Science (IOCS), 2023)
This research is backgrounded by a phenomenon that the problem now is that many people in general have dropped the choice of saving and borrowing money at financial institutions other than shari'a banks, many of the people save in conventional banks and borrow in general cooperatives, even though in conventional banks it is known to adhere to The flower system that according to some scholars, the flower system is among those forbidden because flowers are categorized as usury. Based on this phenomenon, a Shari'a Bank Policy Strategy is needed in increasing public interest in becoming customers at PT. Bank Muamalat Binjai Branch (Case Study on Educators of Al Kaffah Binjai Waqf Foundation). In this study, it uses a qualitative approach and uses a descriptive method. Data collection methods use observation, interviews, documentation. Data analysis techniques use data reduction, data presentation and drawing conclusions/verification. The policy strategy of the syari'ah bank in increasing public interest in becoming customers is through outreach. In order for the implementation of the socialization carried out by Bank Muamalat to run smoothly, managers or employees of Bank Muamalat Binjai Branch must know their duties and know the procedures for outreach to the community so that what they convey can reach the community.